(untitled) (Journal of Maternal and Child Health, 2024)
Background: Stunting is a condition where children’s growth fails (body and brain growth) due to malnutrition for a long time. The incidence of stunting in toddlers needs special attention because it can hinder children’s physical and mental development. This study aims to analyze and estimate the effect of protected wells and the measles vaccine on the incidence of stunting in children under five, with a meta-analysis based on primary studies conducted previously. Subjects and Method: Meta-analysis was carried out in PICO format. Population: Children under five. Intervention: Protected Wells and Measles vaccine status. Comparison: Unprotected Well and Status not vaccinated against measles. Outcome: Stunting incidence. Article searches were carried out using several databases such as Google Scholar, PubMed, Science Direct, and Springerlink. The keywords used are "Protected well" AND Measles vaccine" AND "Stunting in toddlers". Inclusion criteria for the included articles were full-text articles with a cross-sectional design from 2015 to 2023. This study was conducted following PRISMA flow diagram guidelines. Data was analyzed using the Review Manager 5.3 application. Results: 12 cross-sectional studies from Asia and Africa were selected for meta-analysis. the total sample was 48,128 toddlers. Protected well (aOR= 0.86; 95% CI= 0.75 to 1.00; p= 0.040) and measles vaccine (aOR= 0.59; 95% CI= 0.27 to 1.29; p= 0.190) reduce the risk of stunting in children under five. Conclusion: Protected wells and administering the measles vaccine reduce the incidence of stunting in toddlers.